Kemampuan Perawat Dalam Menerapkan Patient Centered Care Di RSUD Dr. M. Haulussy Ambon - Hasna Tunny; Dan Tandi; Puput Inggrid Massa (Jurnal Rumpun Ilmu Kesehatan, 2022)
Patient-focused services or commonly called Patient Centered Care (PCC) have become the main focus in providing health care today. The PCC concept was first introduced by Picker in 1988 through the Picker Institute Europe in England. Regional General Hospital (RSUD) Dr. M Haulussy Ambon is a hospital that has been accredited and is required to be able to implement PCC in its services. Purpose this study was to determine the ability of nurses to apply PCC at RSUD dr. M. Haulussy Ambon. The research design used is descriptive quantitative using observational. The population in this study were nurses at RSUD Dr. M Haulussy Ambon as many as 302 nurses. The number of samples is 113 respondents. data collection techniques using a questionnaire. Results: Most of the nurses' ability to apply PCC showed good results but there were still a number of PCC dimensions that had sufficient results. The PCC dimensions that get good results are respecting patient choices and assessments, physical comfort, information and education, service coordination, and involving family and friends. It can be concluded that most nurses are capable of implementing PCC.